Comparative evaluation between the Vitapan Classical and 3D-Master color scales - Rubens da Rocha Portal Junior; Antonio Renato Melo Rodrigues; Bruno Pereira Alves; Alysson Cruz de Freitas (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate the use of two scales as regard efficiency of color selection and the selection technique used by dental surgeons that practice in the municipality of Belém in the State of Pará, and last year Dentistry students at the Centro Universitário do Pará - Brazil. Method: Four healthy maxillary anterior teeth were chosen in two volunteers. The teeth were submitted to color selection by threeprofessionals experienced in dental prosthesis. Among the interviewees, there were 30 were professionals and 15 academics, and the scales analyzed were Vitapan Classical and Vitapan 3D-Master. A questionnaire containing seven questions on the color selectiontechnique was applied, in which the following factors were analyzed: room, light source, ideal time, and whether the teeth were humid,as well as other requirements for correct color selection. The data obtained were submitted to the Mann-Whitney nonparametric test (5%) as it concerned an independent variable and subjective data. Results: The results showed that there were no statistically significant differences between the scales researched when color selection wasmade with an unsuitable technique and that dental surgeons and academics need to improve their color selection technique. Conclusion: It was concluded that there is no difference between the use of the Vitapan Classical and Vitapan 3D-Master scales when thetechnique used does not follow ideal selection patterns, the number of errors being statistically higher than the number of correct choices, indicating a need for technical improvement in color selection by dental surgeons and academics.